Self-Managing Postoperative Pain with the Use of a Novel, Interactive Device: A Proof of Concept Study. (30th April 2016) - Mordecai, Luke; Leung, Frances H. L.; Carvalho, Clarissa Y. M.; Reddi, Danielle; Lees, Martin; Cone, Stephen; Fox, Zoe; Williams, Amanda C. de C.; Brandner, Brigitta
Abstract : Background . Pain is commonly experienced following surgical procedures. Suboptimal management is multifactorial. Objectives . The primary objective was to assess whether patients used a device (Navimed) to self-report pain over and above a normal baseline of observations. Secondary outcome measures included comparison of pain scores and patient use of and feedback on the device. Methods . In a prospective randomized controlled trial, elective gynaecological surgery patients received standard postoperative pain care or standard care plus the Navimed, which allowed them to self-report pain and offered interactive self-help options. Results . 52 female patients, 26 in each of device and standard groups, did not differ in the frequency of nurse-documented pain scores or mean pain scores provided to nurses. The device group additionally reported pain on the device (means 18.50 versus 11.90 pain ratings per day, t ( 32 ) = 2.75, p < 0.001 ) that was significantly worse than reported to nurses but retrospectively rated significantly less anxiety. 80% of patients found the device useful. Discussion and Conclusion . This study demonstrates that patients used the Navimed to report pain and to help manage it. Further work is required to investigate the difference in pain scores reported and to develop more sophisticated software.